2019
DOI: 10.1002/ehf2.12542
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in patients with heart failure: an international study

Abstract: Aims Cognitive impairment (CI) in heart failure (HF) patients has mostly been studied in single countries in specific health care settings. Sociodemographic and clinical predictors of the global CI and CI dimensions are still unclear. We described CI in a diverse HF population recruited in several countries and in different health care settings and investigated sociodemographic and clinical factors associated with the global and specific CI dimensions in HF patients. Methods and results A secondary analysis fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…It assesses multiple cognitive domains including memory, language, executive functions, visuospatial skills, calculation, abstraction, attention, concentration, and orientation. As many other studies (27,28), we used the original cutoff proposed by the author of the test (25), who recommended that a total MoCA score of <26 indicates the presence of cognitive deficits; furthermore, according to the author, one point should be added to the total score in subjects with a low (<12 years) education level.…”
Section: Methodsmentioning
confidence: 99%
“…It assesses multiple cognitive domains including memory, language, executive functions, visuospatial skills, calculation, abstraction, attention, concentration, and orientation. As many other studies (27,28), we used the original cutoff proposed by the author of the test (25), who recommended that a total MoCA score of <26 indicates the presence of cognitive deficits; furthermore, according to the author, one point should be added to the total score in subjects with a low (<12 years) education level.…”
Section: Methodsmentioning
confidence: 99%
“…Our participants felt particularly at risk for both the frailty due to their health conditions and for the relevant changes in the healthcare systems, where routine visits, rehabilitation programs, and non-urgent care were postponed, leaving these patients to worry if they could get care in case of HF exacerbation or other health emergencies. Prior studies had already reported that patients with HF felt vulnerable on multiple levels (Hauptman, 2018;Sloan & Pressler, 2009) because of financial instability, impaired cognition, and reduced quality of life and social functioning (Sloan & Pressler, 2009;Vellone et al, 2020). Also, it is known that psychological problems such as anxiety and depression were already widespread in this population before the pandemic (Dellafiore et al, 2019), with an 11% to 63% rate of anxiety and an 11% to 51% rate of depression (Bordoni et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is also a lack of standardisation of the cognitive assessment tools used. For example, screening tests such as the Mini Mental State Examination (MMSE) [ 6 ], Montreal Cognitive Assessment (MoCA) [ 7 , 23 ] and Hodkinson Abbreviated Mental Test (AMT) [ 3 , 13 ] were used by some investigators to assess CI, while others used more comprehensive neuropsychological batteries [ 2 , 19 , 24 , 25 ]. Recognising these limitations, CI at least appears to be common in HF and is present across a wide age range.…”
Section: Epidemiology Of Hf and Prevalence Of CImentioning
confidence: 99%
“…Cognitive impairment (CI) in patients with heart failure (HF) is common, with a reported prevalence of 20–80% [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Patients with HF demonstrate increased cognitive deficits compared to controls in several cognitive domains [ 9 ] and have poorer self-care and treatment adherence [ 10 ].…”
Section: Introductionmentioning
confidence: 99%